Analysis of EL emitted by LEDs on Si substrates containing GeSn/Ge multi quantum wells as active layers - Schwartz, Bernhard; Saring, Philipp; Arguirov, Tzanimir; Oehme, Michael; Kostecki, Konrad; Kasper, Erich; Schulze, Jörg; Kittler, Martin (Solid State Phenomena, 2016)
We analyzed multi quantum well light emitting diodes, consisting of ten alternating GeSn/Ge layers, were grown by molecular beam epitaxy on Si. The Ge barriers were 10 nm thick and the GeSn wells were grown with 7% Sn and thicknesses between 6 and 12 nm. Despite the high threading dislocation density in the range of 109 cm-2 the electroluminescence spectra measured at 300 and 80 K yield a broad and intensive luminescence band. Deconvolution revealed three major lines produced by the GeSn wells that can be interpreted in terms of quantum confinement. Biaxial compressive strain causes a splitting of light and heavy holes in the GeSn wells. We interpret the three lines to represent two direct lines, formed by transitions with the light and heavy hole band, respectively, and an indirect line.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Electroluminescence (EL); Ge on Si; Ge; Germanium; Light Emitting Diodes (LED); Multi-quantum-well (MQW); Silicon Photonics